Spatial planning, territorial development, and territorial impact assessment - Medeiros, E. (Journal of Planning Literature, 2019)
This article debates the possibilities and advantages of using territorial impact assessment (TIA) policy evaluation methodologies to assess the implementation of spatial planning instruments. It builds on existing literature to define key analytical goals, dimensions, and respective components to monitor and evaluate the implementation of spatial plans, at all territorial levels, to be used as a TIA evaluation matrix. It concludes that, despite the inherent complexity associated with the process of evaluating spatial planning processes, there are manifest advantages to using TIA tools to evaluate them, mostly at the ex post phase.